The Importance of Digital Skills in Firms’ Innovation: The Case of Western Balkans - Lura Rexhepi Mahmutaj; Nora Jusufi (Journal of Technology Management & Innovation, 2023)
This study analyzes data from 998 SMEs in the Western Balkans using probit regression analysis to explore the significance of digital skills in driving innovation. The findings indicate that variables such as offering staff training, operating in different Western Balkan countries (compared to the reference category), being in the manufacturing sector, and implementing concrete measures for digital skills have statistically significant effects on firms' probability of innovating. These results offer valuable insights to businesses, encouraging them to capitalize on the opportunities presented by emerging digital technologies and the ongoing trend of digitalization across industries. This study confirms the pivotal role of digital skills to the development of innovative products and services, enhancing business performance and our understanding of the interconnectedness between digital technologies, innovation, and digital skills in SMEs.